(untitled) (Fiep Bulletin - online, 2013)
This study had as objective to analyze the waist-height index (WHI) with the total fat and centralized measured by the absorptiometry x-ray of dual-energy (AXDE), and also identifying the prevalence of health risk associated with WHI. It is a study correlational descriptive and 45 young men with age between 20 and 30 years, participated in the study. The variables in study were total body mass (kg), stature (cm), circumference of the waist (CW), percentage of total fat (%G ) and percentage of fat of the trunk TOTAL (%G ) measured by AXDE and WHI. To verify the relationship between the WHI and %G and %G , the lineal correlation of TRUNK TOTAL TRUNK Pearson (p>0, 01) was used as well as the analysis of simple lineal regression, being calculated later the test t of Student, the deterministic index (R2) and the constant error (CE). The results demonstrated a strong correlation between WHI and %G (r=0, 89; TOTAL p <0, 01) and between WHI and %G (r=0, 86; p <0, 01). In the analysis of prevalence of risk to the health, adopting the criterion the TRUNK WHI 0, 5, it was observed that 73, 33% (n=33) of the sample presented superior value to the reference one. There were no differences of averages between the values measured by AXDE and the estimated by the predictive equations developed. The values of R2=0,73 (E1) and R2=0,78 (E2) indicate that in the sample observed 78% and 73%, respectively, of the variation of %G and %G can be TRUNK TOTAL explained by a lineal relationship which involves the WHI. Thus, it was concluded that WHI presents strong correlation values and a good explanatory power of G and G in adult men with age varying among 20 to 30 years, also coming as an effective variable TRUNK TOTAL identifying the risk to the health associate to the excess of centralized fat.